The struggle and enrichment of play: Domestications and overflows in the everyday life of gamer parents - Ask Kristine; Sørenssen Ingvild Kvale; Moltubakk Stine Thordarson (Nordicom Review)
Gaming is a frequent source of conflict for families. Research on parents and gaming has identified a lack of gaming-related expertise, a general devaluation or fear of play, and authoritative and restrictive parenting styles as key sources of conflict. What happens when these deficits are addressed? What does mediation look like when parents are expert gamers, enjoy play, and encourage play for their children? Based on qualitative interviews with 29 parents who identify as gamers, we explore how gamer parents domesticate games. To explore the work of stabilising gaming as a wholesome and valued pastime, we combine domestication theory with overflows to address the struggles involved. The analysis investigates how gamer parents mediate play, with an emphasis on how games are interpreted, the family's player practices, and the role of gaming-related expertise in accordance with the three dimensions (symbolic, practice, cognitive) of domestication theory.